UPAYA PREVENTIF STUNTING ANAK: KOLABORASI SKRINING ANTROPOMETRI DAN PRILAKU ORANGTUA SEBAGAI GARDA TERDEPAN - Ambarwati, Rini; Rokhmah, Nisa Najwa; Andini, Septia; Fatmi, Mindiya; Herlina, Nina; Rikkit; Nurhikmah, Wilda; Wahyuningrum, Cyntia; Nurmala, Sara (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Stunting remains a serious chronic nutrition problem in Indonesia, with long-term impacts on children's physical growth and cognitive development. Despite the improvements shown in the 2024 Indonesian Nutrition Status Survey (SSGI), achieving the target of 14.2% by 2029 requires further efforts. This community service activity aims to conduct early detection through anthropometric screening and provide nutrition education to parents in Pakansari Village, Cibinong, Bogor. Methods include measuring weight and height, as well as administering questionnaires on children's dietary and caregiving practices. Screening results showed most children had adequate nutritional status, though cases of malnutrition and stunting were still present. There is a gap in parental knowledge of balanced nutrition, highlighting the need for increased nutritional literacy. Continuous nutrition education and credible digital media utilization can strengthen family roles in stunting prevention. This initiative contributes to reducing stunting prevalence by enhancing community nutritional awareness.